Freedom of Choice in the Activity - A Pedagogical Condition for Stimulating Students' Motivation for Discovery Learning - Sadovei, Larisa; Țicău , Alexandru-George (Didactica Danubiensis, 2025)
Objectives: The objectives of the research are to highlight the role of freedom of choice in activity as a central element in stimulating motivation for discovery learning; arguing the importance of this pedagogical condition in creating a flexible educational framework adapted to the pace, interests, and cognitive needs of students; identifying the dimensions and principles of applying freedom of choice in the instructional-educational process. Prior Work: Previous studies present the authors' views on student autonomy, experiential learning, and pedagogical constructivism. The paper is based on relevant theories and research (Deci & Ryan, 1985; Kolb, 1984; Piaget, 1965; Bruner, 1970; Vygotsky, 1978; Eccles & Wigfield, 2002), which show that offering personalized options stimulates student initiative, active involvement, and self-regulation. Approach: The methodological approach involved a critical analysis of the specialized literature, theoretical synthesis, comparison of explanatory models, and the development of a conceptual framework applicable to freedom of choice in discovery learning. Results: The research results show that integrating freedom of choice into activities increases intrinsic motivation, cognitive and affective involvement, and the adaptation of the learning process to individual characteristics. The curricular, methodological, and psycho pedagogical dimensions support a student-centered educational process oriented toward active learning. Implications: The results can support the design of educational activities, teaching strategies, and school curricula that promote autonomy and personalized learning, contributing to the optimization of the school climate and the strengthening of long-term motivation. Research Value: The study lies in highlighting freedom of choice as an essential pedagogical principle for stimulating motivation and developing the skills necessary for lifelong learning.